2011
DOI: 10.1111/j.1467-9817.2010.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐language transfer of morphological awareness in Chinese–English bilinguals

Abstract: This study examined cross-language transfer of morphological awareness in Chinese-English bilingual children. One hundred and thirty-seven first to fourth graders participated in the study. The children were tested on parallel measures of compound awareness, vocabulary, word reading and reading comprehension in Chinese and English. They also received measures of English derivational awareness, English phonological awareness and nonverbal reasoning. Structural equation modelling was used to compare a baseline m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
132
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(146 citation statements)
references
References 60 publications
14
132
0
Order By: Relevance
“…However, compound awareness was not found to have a signifi cant eff ect on English vocabulary depth. Recent studies confi rmed that cross-linguistic compound awareness in both Chinese and English significantly contributed to Chinese vocabulary knowledge (e.g., Chen et al, 2009;Liu & McBride-Chang, 2010;Pasquarella, Chen, Lam, Luo, & Ramirez, 2011;Zhang, 2015) and cross-linguistic derivational awareness was found to significantly predict English vocabulary development (Kieffer & Lesaux, 2012;Zhang, 2013). The current study also justified that there were cross-linguistic variations of morphological awareness in vocabulary development, and English compound awareness was a weaker predictor of ESL vocabulary knowledge compared with English derivational awareness.…”
Section: Discussion and Conclusion The Role Of Derivational Awarenesssupporting
confidence: 60%
“…However, compound awareness was not found to have a signifi cant eff ect on English vocabulary depth. Recent studies confi rmed that cross-linguistic compound awareness in both Chinese and English significantly contributed to Chinese vocabulary knowledge (e.g., Chen et al, 2009;Liu & McBride-Chang, 2010;Pasquarella, Chen, Lam, Luo, & Ramirez, 2011;Zhang, 2015) and cross-linguistic derivational awareness was found to significantly predict English vocabulary development (Kieffer & Lesaux, 2012;Zhang, 2013). The current study also justified that there were cross-linguistic variations of morphological awareness in vocabulary development, and English compound awareness was a weaker predictor of ESL vocabulary knowledge compared with English derivational awareness.…”
Section: Discussion and Conclusion The Role Of Derivational Awarenesssupporting
confidence: 60%
“…This will in turn facilitate the design of suitable education and intervention programs for bilingual Chinese-speaking students. Previous studies on cross-linguistic transfer between Chinese and English show large variation both in the specific linguistic domains examined and in results (e.g., Gottardo et al, 2001;Pasquarella et al, 2011;Wang, Cheng & Chen, 2005;Yeung & Ganotice, 2014;Zhang & Koda, 2014). A meta-analysis can provide a comprehensive review of the literature and quantify evidence of linguistic of transfer across multiple studies.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that compound awareness in Chinese L1 predicted English L2 reading acquisition. However, inflectional and derivational awareness in Chinese did not show a significant cross-linguistic relationship with English reading abilities (Chung & Ho, 2010;Luo et al, 2014;Hu, 2013;Pasquarella et al, 2011;Zhang, 2013;Zhang & Koda, 2014;Zhang et al, 2010). There is some indication that these findings are affected by the morphological structure of the typologically distinct languages (Zhang & Koda, 2014;Zhang, 2013): The derivational process in Chinese is very limited, with few derivational affixes, of little functional salience.…”
Section: Transfer Between Logographic Languages and Englishmentioning
confidence: 86%